Download presentation

Presentation is loading. Please wait.

Published byPaul Brass Modified about 1 year ago

1
Gray Case1 The Gray Case Let us assume that the opacity is independent of frequency: Κ ν → Κ NB: This does not mean I ν = I, that is, the intensity (flux, etc) ARE frequency dependent.

2
Gray Case2 Equation of Transfer Assume Radiative equilibrium

3
Gray Case3 Continuing: Assume LTE ==> S ν = B ν ==> J(τ) = S(τ) = B(τ) But B(τ) = σT 4 /π Remember:

4
Gray Case4 On We Go... Now Integrate over all solid angles:

5
Gray Case5 More Equations! Multiply by μdω/4π (i.e.. Take the 1 st moment) Note: Therefore:

6
Gray Case6 Make An Assumption! To proceed further (to this point we have been rather rigorous (e.g., we assume LTE and radiative equilibrium but do everything else properly). In the interior of a star I ≠ f(θ) so consider K = 1/4π ∫I(θ) cos 2 θdω But if I ≠ f(θ) then

7
Gray Case7 What About J? If I ≠ f(θ) then J = I/4π∫dω = I but this means K → J / 3 Here’s the approximation: K = J/3 everywhere. This is called the Eddington Approximation. dK/dτ = H dJ/dτ = 3H or J = 3Hτ + C Now Let us Consider the Intensities

8
Gray Case8 Gray Case Intensity We will consider that I ≠ f(θ) except for the general distinction between an inward and an outward flow: I(θ) = I 1 : 0 < θ < π/2 Outward = I 2 : π/2 < θ < π Inward We shall also assume that at the surface that I is constant over the hemisphere and that there is no inward flux (I 2 = 0) so

9
Gray Case9 Continuing On.... What we want is the constant is the constant in J = 3Hτ + C At the Surface I 2 = 0 so J 0 = I 0 /2 H 0 = I 0 /4 which means H 0 = J 0 /2 So J = 3Hτ + C evaluated at τ=0 (the surface) yields: 2H = C J(τ) = 3Hτ + 2H = H(3τ + 2) But note that F A = 4H so J(τ) = (F/4)(3τ + 2)

10
Gray Case10 The T - τ Relation A Relation of Fundamental Importance is the relation between the temperature T and the optical depth τ. For the Gray Case: J(τ) = H(3τ + 2) But in LTE: J = B B(T) = H(3τ + 2) But this is the Integrated B = σT 4 /π so σT 4 /π = H(3τ + 2)

11
Gray Case11 More on T-τ At τ 0 = 0 we have σT 0 4 /π = 2H so σT 4 /π = 3Hτ + 2H = σT 0 4 /π + 3/2 σT 0 4 /π τ T 4 = T /2 T 0 4 τ = T 0 4 (1 + 3/2 τ) But what is T 0 ? Well remember that F P =4πH = σT 4 and F A = 4H = σT 4 /π The definition of T eff is F P = σT eff 4 2H = σT eff 4 /2π = σT 0 4 /π

12
Gray Case12 The T-τ Relation For the Sun T eff = 5740 K which yields T 0 = 4826 K so to specify the temperature structure T 4 = 1/2 T eff 4 (1 + 3/2 τ) NB: T = T eff at τ = 2/3

Similar presentations

© 2017 SlidePlayer.com Inc.

All rights reserved.

Ads by Google